Architecting a portfolio of systems. Issue 4 (17th April 2019) - Maier, Mark W.
Abstract: A "portfolio‐of‐systems" is a collection of systems related by common management and budgeting, and at least some relationship to mission or missions. A portfolio‐of‐systems describes the not uncommon situation where an office is responsible for multiple systems in multiple phases of development but those systems are not related by common design, common manufacturing, or necessarily interconnected operationally. The relationship is fundamentally one of management, although other linkages might be present or designed if such additional linkages are deemed beneficial. The portfolio‐of‐systems concept differs from systems‐of‐systems and product‐line or family‐of‐systems constructs. This paper describes generalizations of architecting techniques for portfolio situations, particularly recognizing the presence of many largely independent components in multiple stages of development with an ongoing or episodic process. The paper presents two case studies of actual portfolios: One a portfolio of operational demonstration systems and the other a portfolio of weather satellites.